Widespread infection with hemotropic mycoplasmas in bats in Spain, including a hemoplasma closely related to "Candidatus Mycoplasma hemohominis". (April 2015) - Millán, Javier; López-Roig, Marc; Delicado, Verónica; Serra-Cobo, Jordi; Esperón, Fernando
Highlights: Two clades of hemoplasmas infected 97% of 31 bats captured in three caves in Spain. One clade was 97% similar to the human pathogen Candidatus Mycoplasma hemohominis. The only case of a human infected with CMh may be a result of spillover from bats. The second clade had 90.6% identity with a Mycoplasma sp. from bats in the USA. This clade represents a potentially novel hemoplasma species. Abstract: Molecular analyses of blood samples revealed infection with hemoplasmas in 97% of 31 cave bats captured in three caves in North-Eastern Spain. The characterization of 1250 bp of the 16S rRNA gene in 29 of the positive bats identified two different groups of sequences. Twenty-two Schreibers' bats ( Miniopterus schreibersii ) and one long-eared bat ( Myotis capaccinii ) shared one group, composed of seven closely related sequences. These sequences showed an identity of about 97% with " Candidatus Mycoplasma hemohominis" and the phylogenetic branch including bat and human sequences showed a 100% bootstrap value, supporting a close phylogenetic relationship between these hemoplasmas. The second group, representing a potentially novel species, was composed of a single sequence shared by six Schreibers' bats that had 91% identity with the recently reported hemoplasma from little brown bats in North America. Large bat aggregations in roosting caves probably benefits intra and inter-species transmission explaining the high observed prevalence.